2021
DOI: 10.33096/smj.v1i02.44
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Pengolesan Edible Coating Terhadap Ketahanan Warna Plat Akrilik Heat Cured Direndam Kopi Robusta

Abstract: Pendahuluan: Resin akrilik yang paling sering digunakan sebagai basis gigi tiruan adalah resin akrilik heat cured. Namun mempunyai beberapa kelemahan yaitu adanya porositas yang dapat menyebabkan perubahan warna. Tujuan Penelitian: Untuk mengetahui perbedaan pengolesan ediblecoating terhadap ketahanan warna plat resin akrilik heat cured yang direndam di kopi robusta. Bahan dan Metode: Penelitian menggunakan sampel resin akrilik heat cured berbentuk plat dengan ukuran 20mm X 20mm X 2mm sebanyak 32 yang dibagi m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…In accordance with Sugita's research (2009) reported that chitosan has a high absorption capacity ability and chitosan is often used as an effort to remove dyes in textile waste so that there is a possibility that with a high level of chitosan absorption there is an absorption of tannins from coffee into PMMA denture base materials that can cause discolourization. [20] The obtained results were not consistent with the statement that chitosan possesses high chemical reactivity due to the presence of other compounds, such as the amine group (NH2), which allows it to bind water effectively. [11] Ismayati T (2017) mixing PMMA and chitosan with various concentrations of hardness with material A in the form of chitosan with acetic acid solvent and B material chitosan acrylic acid acetone solvent.…”
Section: Discussionmentioning
confidence: 69%
“…In accordance with Sugita's research (2009) reported that chitosan has a high absorption capacity ability and chitosan is often used as an effort to remove dyes in textile waste so that there is a possibility that with a high level of chitosan absorption there is an absorption of tannins from coffee into PMMA denture base materials that can cause discolourization. [20] The obtained results were not consistent with the statement that chitosan possesses high chemical reactivity due to the presence of other compounds, such as the amine group (NH2), which allows it to bind water effectively. [11] Ismayati T (2017) mixing PMMA and chitosan with various concentrations of hardness with material A in the form of chitosan with acetic acid solvent and B material chitosan acrylic acid acetone solvent.…”
Section: Discussionmentioning
confidence: 69%